Transforming India into a Transshipment hub- Government Initiatives and Experience - Dorathy, M.Bina Celine; David, Prabhakar Christopher (International Journal of Psychosocial Rehabilitation, 2020)
With its long coastline and strategic location, India is supposed to be in a dominant position in maritime transportation. But due to poor infrastructure and policy framework, the country extensively depends on other maritime nations such as Singapore and Colombo for transshipment. This increases the cost of exports and importsthereby placing India at a disadvantage in the global market. In response to this alarming situation, the government has taken a major initiative to promote three transshipment ports with world class facilities in the southern part of India. It is expected that these ports would compete with other transshipment ports, particularly withColombo, andbring thetransshipped cargo back to India.